2017
DOI: 10.1002/pssa.201700250
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Laser Wavelength on the Optical and Electronic Properties of Black Diamond

Abstract: Black diamond, obtained by femtosecond laser treatment of natively transparent diamond, is a promising material for solar applications. The enhancement of the interaction between the active material and the solar spectrum is obtained by a controlled texturing of the diamond surface at the nanoscale, the impact of which on the optical and electronic properties of the bulk material is strongly influenced by the laser parameters. In this work, the properties of black diamond samples obtained by using two differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Subsequent studies confirmed that HSFL on diamond (similarly to SiC) is generated with periodicities that are strictly connected to the incident laser beam wavelength. By decreasing λ to 400 nm, Girolami et al were able to fabricate LIPPS with a periodicity of approximately 80 nm [69], thus confirming the expected value of λ/2n, (n = 2.46 for diamond at the wavelength of 400 nm), as it is shown in Figure 4. The experimentally validated relationship suggests that it is possible to finely modulate the texturing periodicity of diamond by selecting the proper laser wavelength to be used.…”
Section: Institute Of Physicssupporting
confidence: 65%
“…Subsequent studies confirmed that HSFL on diamond (similarly to SiC) is generated with periodicities that are strictly connected to the incident laser beam wavelength. By decreasing λ to 400 nm, Girolami et al were able to fabricate LIPPS with a periodicity of approximately 80 nm [69], thus confirming the expected value of λ/2n, (n = 2.46 for diamond at the wavelength of 400 nm), as it is shown in Figure 4. The experimentally validated relationship suggests that it is possible to finely modulate the texturing periodicity of diamond by selecting the proper laser wavelength to be used.…”
Section: Institute Of Physicssupporting
confidence: 65%
“…This implies that samples treated under a compressed air flow or a N 2 flow are subjected to approximately the same amount of tensile stress, whereas the sample treated under a He flow is subjected to a compressive stress. It is worth mentioning here that an upshifted diamond Raman peak, denoting a compressive stress as in the case of TM3-He, has been observed in all the UHV-fabricated black diamonds, showing the best LIPSS in terms of geometrical regularity and structural integrity [ 2 , 3 , 6 , 24 ]. Conversely, a downshifted diamond Raman peak, denoting a tensile stress as in the case of TM1-air and TM2-N 2 , has only been observed in “thermal management grade” black diamond plates UHV-treated at high values of total accumulated laser fluence (>10 kJ/cm 2 ), which resulted in a very damaged and irregular surface [ 2 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…First, LIPSS acts as a diffraction grating for the impinging photons, thus enhancing light trapping [ 23 ]; in this sense, it is crucial to ensure regular, well-defined structures uniformly distributed over the largest possible area of the treated material, aimed at minimizing the escape probability of coupled light. Moreover, by unavoidably creating defects, fs-laser treatments always introduce energy levels within the semiconductor bandgap, which are eventually responsible for photon absorption [ 24 ]. In a few words, in black diamond films for solar applications, LIPSS-induced light trapping increases the optical path length (i.e., the distance that an unabsorbed photon may travel within the material before escaping out), thus increasing the probability for solar photons to be absorbed by sub-bandgap defect-related energy levels introduced by the laser treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By decreasing the laser wavelength from 800 to 400 nm, Equation (1) was found to be confirmed. A periodicity of about 80 nm was obtained at λ = 400 nm, where diamond refractive index is 2.46, under similar conditions of absorbed accumulated fluence with respect to 800 nm [69]. Consequently, the validity of Equation (1) suggests that a precise value of texturing periodicity can be controlled a priori by selecting the laser wavelength.…”
Section: Black Diamond Filmsmentioning
confidence: 80%